Hamārā klāsīkī adab aur taraqqī pasand tanqīd (Ġālib Insṭīṭiyūṭ, 2014)
Papers presented at the seminar on
Includes bibliographical references. - In arab. Schrift, Urdu. - Title on t.p. verso in roman: Hamara classiki adab aur taraqqi pasand tanqeed
Keywords: Konferenzschrift; Urdu literature